Overview of Maternal First Aid For Children With Wounds At Home - Pratiwi, Tiara Indah; Rachmawati, Dewi; Mulyadi, Arif (Health Gate, 2025)
Mothers didn't know how to give wound first aid properly. Improper handling of wounds can cause the wound healing process to be prolonged. This study aims to determine the description of mothers' first aid for children who experience wounds at home. The research design used was quantitative descriptive with a sample of 31 people selected using quota sampling technique. Data collection was carried out on January 17 - February 17, 2024 by dor to dor in the Jatitengah Village. The instrument used was an observation sheet using a measuring instrument 3 Standard Operating Procedures (SOP) on bruises, open wounds, and burns. The results of this study showed 96.8% were lacking in handling bruises, 54.8% were lacking in handling open wounds and 80.6 were lacking in handling burns. The overall ability of mothers in providing first aid 90.3% (n = 28) have less ability, 9.7% (n = 3) of respondents have sufficient ability. The overall ability of mothers in providing first aid 90.3% (n=28) had less ability, 9.7% (n=3) of respondents had sufficient ability. The conclusion of this study is that almost all respondents get less ability due to lack of information about first aid, low education level and belief in using traditional methods. Therefore, it is necessary to educate health workers (Nurses) to mothers in order to improve the ability of mothers, so as to minimize more severe complications from the occurrence of wounds.